If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9-2x=x
We simplify the equation to the form, which is simple to understand
9-2x=x
We move all terms containing x to the left and all other terms to the right.
-2x-1x=-9
We simplify left and right side of the equation.
-3x=-9
We divide both sides of the equation by -3 to get x.
x=3
| 6+5x=x | | x-2(x-1)=4-3(x-2) | | 13-8z=7 | | 12+5=11+12x | | -3(x-7)+2= | | 9(2-a)=63 | | 3(2+5m)=-54 | | 17(x-2)=34 | | 17(x-2)= | | 10-2(x+3)=3+3(2x+5) | | 4b-(9b-8)= | | 3x^2+10x+5=0 | | 379.94=3.14*r^2 | | 4+45=8x+13 | | 2x-5x=x+8 | | 4x+10=2x+29 | | -7y-(2y+4)= | | 4x^2+13=3 | | 2x^2=162 | | 5-4(x+1)=4x-3(4x-1)-4 | | 9+3b=18 | | 9+3b=15 | | 75.36=2r*3.14 | | 5m=10-5m | | 3(x+15)+4(9-x)=0 | | 8r=-4r-12 | | x^2-6=55 | | 0.2x+9=8(0.4x-1) | | -2=3n+6-5n | | 244.92=2r*3.14 | | -3+2x=3x-4 | | 9(3x-1)-5=6x |